Analisis Ekonomi Sektoral Masa Pandemi Covid-19 Di Kabupaten Lombok Timur Tahun 2019-2020 : Tinjauan Shift Share Analysis - Tati Atmayanti (Universitas Hamzanwadi, 2022)
Economic growth during the COVID-19 pandemic in East Lombok Regency decreased by -3.10 percent. The implementation of restrictions on community activities (PPKM) causes limited activities of economic actors, both private and government. This study aims to analyze the shift in economic sectors during the COVID-19 pandemic. Types and approaches of research with quantitative descriptive. The secondary data used is in the form of Gross Regional Domestic Product (GRDP) data at constant prices in 2010 based on business fields to describe employment in East Lombok Regency during the 2019 and 2020 covid-19 pandemic. The data analysis technique uses shift shareanalysis, where this analysis compare GRDP at the national level with levels below it. The shift share analysis technique divides growth into national growth (National Share), industry mix (proportional shift) and competitive advantage/competitiveness (differential shift). Based on the analysis, it is known that the decline or shift towards the negative is of course due to the declining contribution of sectoral economic sectors, especially leading economic sectors, which have a significant impact using shift share such as the manufacturing sector; agriculture, forestry and fishery sectors; construction sector, transportation and warehousing sector and Wholesale and Retail Trade; Car and Motorcycle Repair. The impact of the COVID-19 pandemic has resulted in sluggishness in the economy, which has resulted in a reduction in the workforce, reduced working hours, layoffs and the failure of several businesses in the real sector (goods and services) as well as in the tourism sector.